INOVASI TEKNOLOGI DALAM INDUSTRI HALAL UNTUK MENINGKATKAN KEAMANAN RANTAI PASOKAN INDUSTRI HALAL INTERNASIONAL - Purwati, Dewi; melinasari, Susi; Kartono, Keris (Institut Agama Islam Sahid (INAIS) Bogor, 2026)
The international halal industry continues to grow rapidly, driven by the increasing global demand for halal products that comply with sharia principles. In facing the challenges of supply chain security and transparency, technological innovations such as Blockchain, Internet of Things (IoT), and Artificial Intelligence (AI) play an important role in strengthening the integrity of halal products. This study aims to identify the role of technological innovation in improving the security of the halal supply chain and develop strategies for implementing these technologies on an international scale. The results show that Blockchain enables decentralized and immutable data recording, thereby facilitating the traceability of halal products from upstream to downstream. IoT supports real-time monitoring of product conditions through sensors that monitor temperature, humidity, and potential contamination during storage and transportation. Meanwhile, AI is used to automatically analyze data, detect non-halal ingredients, and accelerate the halal certification process with high accuracy. These technologies not only improve operational efficiency but also strengthen consumer confidence in halal products. However, the implementation of these technologies faces challenges such as limited digital infrastructure, high costs for adoption by MSMEs, and the need for regulatory harmonization between countries. Therefore, a collaborative strategy involving the government, halal certification bodies, industry players, and consumers is needed. Education on the benefits of technology must be improved, while financial support and the development of technology-based global standards need to be prioritized. With the implementation of the right strategy, technological innovation can be a major catalyst in building a modern, trusted, and sustainable international halal industry ecosystem.